Sentencing from There to Here and from Then to Now - Healy, Patrick (Canadian Criminal Law Review, 2013)
Recent amendments have underscored punitive aspects in sentencing. This is apparent in the multiplication of mandatory minimum sentences, restriction of conditional sentences, limitation of credit for pre-sentence custody, and doubling the victim surcharge with no discretion for exemption. Apart from their specific effects, these amendments signal a reorientation of the principles and objectives of sentencing expressed in Part XXIII of the Code and in the jurisprudence that has evolved since 1996. They diminish the importance of rehabilitative and restorative aims in favour of greater retribution. As a result, they alter several principles of sentencing that remain in the Code as they were enacted in 1995 - including proportionality, individualization and totality. [PUBLICATION ABSTRACT]
Num Pages: 14